Dampak Positif Berkembangnya Koperasi Syariah Di Daerah Pemukiman Warga Kota Binjai - Manurung, Khoirul Ardani; Nursantri Yanti (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2023)
The issue at hand in this study is how Islamic cooperatives have helped to advance the welfare and economy of Indonesians. The goal of this study is to inform readers on how sharia cooperatives have shaped business players and society in Indonesia and how they have done so positively. The author uses qualitative research as the method of inquiry. Scientific reasoning is applied in qualitative research. The study's findings indicate that sharia cooperatives can play a role in addressing the community's economic problems. The welfare of the populace will also rotate and be realized if the economic wheel of a nation keeps turning.